Creatives' expectations: The role of supercreatives in cultural district development. (February 2017) - Goldberg-Miller, Shoshanah B.D.; Heimlich, Joe E.
Abstract: In examining the goal of incorporating arts and culture into urban planning, district development and the creation of cultural destinations in cities today, an important element to consider is the role of the so-called "supercreatives, " who are a core part of the creative class. Gaining an understanding of the motivations, expectations, and underlying issues pertaining to these producers of arts and culture – who also may be consumers of creative outputs – can provide a window of opportunity through which to attain valuable perspectives on livability, policy development, and city building. This paper uses data from a survey of 350 attendees at an arts and music festival in a burgeoning arts district in Columbus, Ohio called Franklinton. The area, once a floundering and financially challenged neighborhood, has begun to re-develop and is in transition in large part because of municipal and community-led efforts focused on attracting the creative community and those who follow them. The study looks at what respondents feel will make an arts district successful. An unexpected finding from this study was that the predominance of respondents fell into the class of "supercreatives, " thus giving a very different meaning to the findings, which can importantly inform policy and planning for cultural destinations in urban centers. We find that aspects including a creative focus, walkability, and safety are the key elements that must be included. In addition, the findings show that, while the creative community needs to be involved in the fostering of an arts district, leadership of these initiatives should come primarily from politicians, arts managers, residents, policymakers, businesses, and researchers. Highlights: A creative focus, walkability, and safety are key in fostering arts/cultural districts. Supercreatives' opinions and preferences are valuable in policy development. Hard and soft factors must be considered in planning for the creative class. Actors from all three sectors should lead the cultural district development process.